The Moderating Role Of Government Support On The Effect Of SME’s Internal Factors On Export Performance - Lee, Ming Huoy (2018)
Food processing industry is considered as a value-added business to the Malaysian economy. This research address theoretical framework to describe the relationship between firm characteristics, management characteristics, labour productivity, innovation and moderating effect of government support for food processing SMEs export performance. The new conceptual framework, its help firms to determine the factors that contribute to the success in export performance and effectiveness of government support to food processing SMEs.